Common Fixed Point Theorems on Metric Space for Two and Four maps Using Generalized Altering Distance Functions in Five Variables and Applications to Integral Type Inequalities - K. Sridevi; M. V. R. Kameswari; D. M. K. Kiran (International Journal of Mathematics And its Applications, 2017)
The concept of existence and uniqueness of fixed points by altering distance between points have been explored by many authors. In this paper, we obtain unique common fixed point results for two and four self mappings by altering distances sub compatible functions with generalization of contractive type condition and application to integral type inequalities.